TATHBIQ KITAB AMTSILATY FI TAâ€™LIM QOWAID NAHWIYAH BI MAâ€™HAD AL HAFIDZOH AL ISLAMY AS SALAFI KARANGMENGGAH WONOREJO PASURUAN: ØªØ·Ø¨ÙŠÙ‚ ÙƒØªØ§Ø¨ Ø£Ù…Ø«Ù„ØªÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„ØØ§ÙØ¸Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø§Ù„Ø³Ù„ÙÙŠ ÙƒØ±Ø§Ù†Ø¬ Ù…Ù†Ø¬Ø§Ù‡ ÙˆÙ†ÙˆØ±Ø¬Ùˆ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù† - Masruroh, Luâ€™luil; Aisyiah, Jaziâ€™atul (INTAJUNA : Jurnal Hasil Pemikiran, Penelitian, Produk Bidang Pendidikan Bahasa Arab, 2021)
As we know, every Muslim is required to teach the Qur'an and Sunnah as the main sources of Islamic education. To understand them requires familiarity with Arabic grammar, especially grammar, which in this case requires a long time to learn. Therefore, many scholars make the grammar method easy to teach by students without the need for a long time. One of my example writers is the correct method of teaching grammar without taking a long time. This research aims to 1) describe how to apply education, 2) the problems of education for both teachers and students, and 3) as well as solutions to the problems of teaching grammar using the book Examples in the Institute Portfolio. To achieve the above objectives, the researcher used qualitative research using the qualitative approach. The data collection methods used are observation, interview, and documentation. Data analysis procedures are data collection, data reduction, data presentation and extraction. The results of this research is 1) in the application of the book My examples in teaching grammar rules at the Institute of the portfolio divided into several chapters according to the volume and is implemented according to the guidelines for determining the education book My examples in Dar Al-Falah Jibara. 2) It suffers from several problems, including: (a) lack of faculty members to book examples, (b) lack of optimal time, (c) the learning process is boring, and (d) the level of students' ability varies. 3) Solving problems in the application of the book My Examples is: (a) adding faculty members through alumni or external, (b) increasing the intensity of time, (c) creating a fun learning atmosphere, and (d) forming study groups and discussions for students outside the religious school hour. Ù…Ø³ØªØ®Ù„Øµ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© ÙˆØ³ÙŠÙ„Ø© Ù…Ù† Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªÙŠ ØªØ¹ÙŠÙ† Ø¹Ù„Ù‰ Ø¥Ø¬Ø§Ø¯ Ø§Ù„Ù„ØºØ© ÙˆÙ…Ù…Ø§Ø±Ø³Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙˆØ§Ù„ÙƒØªØ§Ø¨Ø© Ø¨Ù„ØºØ© ØµØÙŠØØ© Ø®Ø§Ù„ÙŠØ© Ù…Ù† Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙˆØªØ³Ø§Ø¹Ø¯ Ø¹Ù„Ù‰ Ø¯Ù‚Ø© Ø§Ù„ØªØ¹Ø¨ÙŠØ± ÙˆØ³Ù„Ø§Ù…Ø© Ø§Ù„Ø¢Ø¯Ø§Ø¡ ÙˆØ¶Ø¨Ø· Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ù„Ø£Ù† Ø¹Ø¯Ù… Ù…Ø±Ø§Ø¹Ø§Ø© Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© ÙŠØªØ±ØªØ¨ Ø¹Ù„ÙŠÙ‡ ÙØ³Ø§Ø¯ ÙÙŠ Ø§Ù„Ù…Ø¹Ù†Ù‰ ÙˆÙ‚Ù„Ø¨ ÙÙŠ Ø§Ù„ÙÙƒØ±Ø© ÙˆØ³ÙˆØ¡ ÙÙŠ Ø§Ù„ÙÙ‡Ù…. Ù„Ø°Ù„ÙƒØŒ ÙØ¥Ù† Ø§Ù„Ø¹Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ ÙŠØ¬Ø¹Ù„ÙˆÙ† Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© Ø³Ù‡Ù„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù† Ù‚Ø¨Ù„ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø¯ÙˆÙ† Ø§Ù„ØØ§Ø¬Ø© Ø§Ù„Ù‰ ÙˆÙ‚Øª Ø·ÙˆÙŠÙ„. Ø£ØØ¯Ù‡Ø§ Ø·Ø±ÙŠÙ‚Ø© ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠ Ù‡Ùˆ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØµØÙŠØ Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© Ø¯ÙˆÙ† Ø§Ù„ØØ§Ø¬Ø© Ø§Ù„Ù‰ ÙˆÙ‚Øª Ø·ÙˆÙŠÙ„. ØªÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù‰ 1) Ù„ÙˆØµÙ ØªØ·Ø¨ÙŠÙ‚ ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„ØØ§ÙØ¸Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø§Ù„Ø³Ù„ÙÙŠ ÙƒØ±Ø§Ù†Ø¬ Ù…Ù†Ø¬Ø§Ù‡ ÙˆÙ†ÙˆØ±Ø¬Ùˆ Ø¨Ø§Ø³Ø±ÙˆØ§Ù†ØŒ 2) Ù„Ù…Ø¹Ø±ÙØ© Ù…Ø´ÙƒÙ„Ø§Øª ØªØ·Ø¨ÙŠÙ‚ ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠ Ù„ÙƒÙ„ Ù…Ù† Ø§Ù„Ù…Ø¹Ù„Ù…ÙŠÙ† ÙˆØ§Ù„Ø·Ø§Ù„Ø¨Ø§ØªØŒ 3) Ù„Ø¨ØØ« Ø¹Ù† ØÙ„ÙˆÙ„Ù‡Ø§. Ù„ØªØÙ‚ÙŠÙ‚ Ø§Ù„Ø£Ù‡Ø¯Ø§Ù Ø§Ù„Ù…Ø°ÙƒÙˆØ±Ø© Ø£Ø¹Ù„Ø§Ù‡ØŒ Ø§Ø³ØªØ®Ø¯Ù…Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ù‡Ùˆ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙŠÙÙŠ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„ÙƒÙŠÙÙŠ. Ø·Ø±Ù‚ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù‡ÙŠ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø©ØŒ Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø©ØŒ ÙˆØ§Ù„ÙˆØ«Ø§Ø¦Ù‚. Ø¥Ø¬Ø±Ø§Ø¡Ø§Øª ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡ÙŠ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§ØªØŒ ØªÙ‚Ù„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§ØªØŒ Ø¹Ø±Ø¶ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØ§Ù„Ù…Ø³ØªØ®Ù„Øµ. Ø£Ù…Ø§ Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ 1) ÙÙŠ ØªØ·Ø¨ÙŠÙ‚ ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„ØØ§ÙØ¸Ø© ØªÙ‚Ø³ÙŠÙ… Ø§Ù„Ù‰ Ø¹Ø¯Ø© ÙØµÙˆÙ„ ØØ³Ø¨ Ø§Ù„Ù…Ø¬Ù„Ø¯Ø© ÙˆÙŠØªÙ… ØªÙ†ÙÙŠØ°Ù‡Ø§ ÙˆÙÙ‚Ø§ Ù„Ø¥Ø±Ø´Ø§Ø¯Ø§Øª ØªØØ¯ÙŠØ¯ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠ ÙÙŠ Ø¯Ø§Ø± Ø§Ù„ÙÙ„Ø§Ø Ø¬ÙŠØ¨Ø§Ø±Ø§. 2) ÙˆØªØ¹Ø§Ù†ÙŠ Ù…Ù† Ø¹Ø¯Ø© Ù…Ø´Ø§ÙƒÙ„ Ù…Ù†Ù‡Ø§: (Ø£) Ù†Ù‚Øµ Ø£Ø¹Ø¶Ø§Ø¡ Ù‡ÙŠØ¦Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ³ ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠØŒ (Ø¨) Ù‚Ù„Ø© Ø§Ù„ÙˆÙ‚Øª Ø§Ù„Ø£Ù…Ø«Ù„ØŒ (Ø¬) Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù…Ù„Ø©ØŒ (Ø¯) ÙŠØ®ØªÙ„Ù Ø§Ù„Ù…Ø³ØªÙˆÙ‰ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø§Ø¨. 3) ØÙ„ÙˆÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ ØªØ·Ø¨ÙŠÙ‚ ÙƒØªØ§Ø¨ Ø§Ù…Ø«Ù„ØªÙŠ Ù‡Ùˆ: (Ø£) Ø¥Ø¶Ø§ÙØ© Ø£Ø¹Ø¶Ø§Ø¡ Ù‡ÙŠØ¦Ø© Ø§Ù„ØªØ¯Ø±ÙŠØ³ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ø®Ø±ÙŠØ¬ÙŠÙ† Ø§Ùˆ Ø®Ø§Ø±Ø¬ÙŠØŒ (Ø¨) Ø²ÙŠØ§Ø¯Ø© Ø´Ø¯Ø© Ø§Ù„ÙˆÙ‚ØªØŒ (Ø¬) Ø®Ù„Ù‚ Ø¬Ùˆ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ù…Ù…ØªØ¹Ø§ØŒ (Ø¯) ØªØ´ÙƒÙŠÙ„ Ù…Ø¬Ù…ÙˆØ¹Ø§Øª Ø¯Ø±Ø§Ø³ÙŠØ© ÙˆÙ…Ù†Ø§Ù‚Ø´Ø§Øª Ù„Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø®Ø§Ø±Ø¬ Ø³Ø§Ø¹Ø© Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¯ÙŠÙ†ÙŠØ©.